1998
DOI: 10.1007/s005860050095
|View full text |Cite
|
Sign up to set email alerts
|

Comparative immunohistochemical study of group II (synovial-type) and group IV (cytosolic) phospholipases A 2 in disc prolapse tissue

Abstract: IntroductionThe PLA2 isoforms include the secretory (also called synovial-type) group II extracellular 14 kD isoform (sPLA2) and the group IV cytosolic 85-110 kD isoforms (cPLA2) [6,21,22].It has been suggested that both types of PLA2 (sPLA2 and cPLA2) are implicated in inflammation. These enzymes catalyze the release of arachidonic acid, which is then converted, for instance, to prostaglandins by the cyclo-oxygenases (COX-1 and COX-2). Thus arachidonic acid mobilization seems to be dependent on both types of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…However, in 1998 it was also reported that two different phospholipase A2 enzymes are present in herniated disc tissue from humans [14] and the difference in inhibitory effects of varying NSAIDs on these two enzyme types is, to our knowledge, still not known.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in 1998 it was also reported that two different phospholipase A2 enzymes are present in herniated disc tissue from humans [14] and the difference in inhibitory effects of varying NSAIDs on these two enzyme types is, to our knowledge, still not known.…”
Section: Discussionmentioning
confidence: 99%
“…The reason for this difference is not known, but it might be related to the fact that ketoprofen and diclofenac belong to different NSAID subgroups and have a different selectivity for the two cyclo-oxygenases COX-1 and COX-2. ica induced by a herniated disc, in both recent and older literature [13,14,15,18,19,24,26,39,44,45,48]. Highdose administration of methylprednisolone, a potent antiinflammatory drug, has been shown in other experiments to reduce nucleus pulposus-induced nerve root injury dramatically [32].…”
Section: Introductionmentioning
confidence: 99%
“…Of note, platelets are a possible source of group II phospholipase A 2 (secretory PLA2: sPLA2), an enzyme that is involved in the amplification of both local and systemic inflammation [1, 7, 8], and has been suggested to be involved in disc pathophysiology and possibly also sciatica [27,29]. Controlled studies have suggested that PLA2 levels are not pathologically high in disc herniation tissue or degenerated discs in comparison with control disc tissues [10,11], and thus alternative sources of PLA2 enzyme, such as release from platelets, may be clinically relevant. PLA2 enzyme has been shown to have deleterious effects on nerve root function and structure in an animal model [5].…”
Section: Discussionmentioning
confidence: 99%
“…Platelets are known to contain both a low molecular weight (14 kDa, sPLA2) and a higher molecular weight (85 kDa, cytosolic: cPLA2) PLA2 enzyme, which are located in the α-granules and the cytosol of platelets, respectively. It has [11]. Platelet activation follows adhesion, which is triggered by damage of the blood vessel wall [22].…”
Section: Discussionmentioning
confidence: 99%